The Effect of Breastfeeding Instruction on the Breastfeeding Benefits for Primiparous Postpartum - Mutiara Dwi Yanti; Riska Fadia; Kholilah Lubis (GLOBAL HEALTH SCIENCE GROUP, 2025)
To determine whether breastfeeding technique education has an impact on the ability of postpartum primiparous mothers to breastfeed successfully. The study was a pre-experiment with only one group of one group pretest-posttest approach. 23 postpartum primiparous mothers were applied in this study using purposive sampling. The study was conducted at the Fitri Asih Clinic, Patumbak District, Deli Serdang Regency in 2024. Data were collected using The Latch Score assessment to identify breastfeeding instructions. The Wilcoxon test was used to analyze the data. There is a difference in the success of breastfeeding in primiparous postpartum mothers before and after receiving breastfeeding technique counseling (p=0.001). Based on the results of the study, the success of breastfeeding in primiparous postpartum mothers at the Fitri Asih Clinic, Patumbak District, Deli Serdang Regency in 2024 was influenced by education on breastfeeding techniques in primiparous postpartum mothers.